COX-2 expression correlation with invasion in human breast carcinomas and in cell line MDA-MB-231 in vitro (Bangladesh Journal of Pharmacology, 2016)
COX-2 expression by means of immunohistochemistry in 120 cases breast invasive ductal carcinomas and 60 cases benign lesions were compared with clinicopathological features and prognostic molecular markers. COX-2 role of invasiveness and chemotaxis in breast cancer cell line MDA-MB-231 by using small RNA interference (siRNA) plasmids to disrupt COX-2 expression in vitro were investigated. The results show that COX-2 immune positivity and percentage of positive cells in breast carcinomas were higher than those in benign lesions and positivity correlated significantly with HIF-1?, VEGF, the grading, metastasis and vascular invasion of carcinoma (p